Ambulatory care of wounds – clients´ profile with chronic lesion. A prospective study - uliana de Oliveira Araújo; Beatriz Guitton Renaud Baptista de Oliveira; Fernanda Ferreira da Silva Lima (Online Brazilian Journal of Nursing, 2008)
Abstratct. This study aims to characterize the clients porters of tissue lesion chronic which are attended in the Repair of Wound Ambulatory of Antonio Pedro University Hospital Aid Center (HUAP), in view of the following variables: age, sex, education, the basic disease, type of wound, time and location of the wound from its beginnings. It is a quantitative, descriptive and exploratory nature study approved by the Ethic in Search Committee (CEP-CCM/HUAP), being developed among 39 injury porter patients attended by the nurse consult, from May 2006 to April 2007. The results show that the population of the study is mostly male (51%), aged from 40 to 59 years (54%) and with incomplete middle (junior high) school (61%). With relation to clinical aspects, 28% get Mellitus Diabetes associated to Systemical Arterial Hypertension, 31% of them presented Mellitus Diabetes and 29% arterial hypertension; 85% having lesion upon the low members, being that 40% were caused by vein ulcers and 33% by diabetes ulcers; 27% showed the lesion from 1 year to 4 year. It was concluded that the systematic monitoring of wounded patients is fundamental not only to treat the wound but also to control basic illnesses and prevent complications. We recommend that new studies be carried out to obtain a more representative profile of this population in the different levels of attention for the health